Corporeidade e conhecimento : diálogos necessários à Educação Física e à escola - Cupolillo, Amparo Villa (2008)
This work wishes to put in contact two fields historically took in opposition: knowledge and body, in order to possibility other kinds of intervention on school that value the human dimensions difference's by witch the knowledge expresses itself, especially those which emerges through the corporality. Basing myself on the everyday scholar, I searched on situations that presented themselves as enigmatic because contradictories and opposites to the linearity and rational order elements that could offer me support to stress this opposition, apparently so solid and truly. Grounded on epistemology of complexity and deeply involved with the studies of everyday, I have elected three suggestive moments experienced through the twenty years of experience on brazilian public schools with the Physic Education discipline, in witch, by my point of view, the dichotomy body/mind shows fragilities. The first has, as a central character, Tomás, an student of the first school that I worked; the second has as subjects the childs of CAIC, a field-school for the discipline Practices of Teaching , by which I am responsible, from the graduation course on Physic Education of UFRRJ; and the third has as a main character Daniel, a student of a public school in which I did the field research of this thesis. Taking into consideration this three situations, the discussion on this study displaced from the notion of subject given by the modernity, that disrespects the complexity of the development and of the genetic and cultural aspects on the constitution of the human being; passes by the examination of the influences from the disciplinal apparatus on school environment, especially those strongly currents on the corporality treatment, following Foucault´s perspective; searches among the more actual debates, based on the Cultural Studies , elements that signalize the richness and the pertinence to the environment school of valorization of many differences of trajectories and developments of human beings; and, finally, with the supports of author's works that comprehend the human being as a bodysubject or a mindincorporated , searches to offer subsidies that promote a disorder on the impermeability conception of knowledge with which the school is working, permitting a larger comprehension of the complexity about what is the human being.